Use of reproductive health services among women using long- or short-acting contraceptive methods - a register-based cohort study from Finland - Saloranta Tuire Helene; Gyllenberg Frida Katrin; But Anna; Gissler Mika; Heikinheimo Oskari; Laine Merja Kristiina (BMC, 2022)
Background: Long-acting reversible contraceptives (LARCs) have superior contraceptive efficacy compared to short-acting reversible contraceptives (SARCs) and choosing LARCs over SARC methods reduces the need for abortion care. However, little is known how initiating these methods associates with the subsequent overall need of reproductive health services including family planning services, and visits for gynecological reasons in primary and specialized care.
Methods: We followed altogether 5839 non-sterilized women aged 15-44 years initiating free-of-charge LARC methods (n = 1689), initiating or switching SARC methods (n = 1524), or continuing with the same SARC method (n = 2626) at primary care family planning clinics in the City of Vantaa, Finland, 2013-2014 for 2 years using Finnish national health registers. We assessed the use of reproductive health services, namely attending public primary or specialized health care for gynecological reasons or attending the family planning clinics by applying unadjusted and adjusted negative binomial regression models on visit counts.
Results: A total of 11,290 visits accumulated during the two-year follow-up: 7260 (64.3%) at family planning clinics, 3385 (30.0%) for gynecological reasons in primary, and 645 (5.7%) in specialized health care. Altogether 3804 (52.4%) visits at the family planning clinics were for routine checkup, and 3456 (47.6%) for other reasons. Women initiating LARC methods used reproductive health services for reasons other than routine checkups similarly as women initiating or switching SARC methods (adjusted incidence rate ratio 0.93, 95% CI 0.82-1.05), while women continuing with SARC methods used the services less frequently (0.65, 0.59-0.72). Women initiating free-of-charge LARC and those continuing with the same SARC method used services less for abortion care than women initiating or switching SARC (adjusted incidence rate ratios 0.05, 95% CI 0.03-0.08 and 0.16, 95% CI 0.11-0.24, respectively).
Conclusions: While women initiating LARC methods have lower need for abortion care compared to women initiating SARC methods, women initiating both LARC and SARC methods have similar overall need for reproductive health services. In contrast, women continuing with their SARC method need reproductive health services less than women initiating LARC or a new SARC method. These service needs should be acknowledged when planning and organizing family planning services, and when promoting long-acting reversible contraception.